2006
DOI: 10.1038/ng1861
|View full text |Cite
|
Sign up to set email alerts
|

A signature of chromosomal instability inferred from gene expression profiles predicts clinical outcome in multiple human cancers

Abstract: We developed a computational method to characterize aneuploidy in tumor samples based on coordinated aberrations in expression of genes localized to each chromosomal region. We summarized the total level of chromosomal aberration in a given tumor in a univariate measure termed total functional aneuploidy. We identified a signature of chromosomal instability from specific genes whose expression was consistently correlated with total functional aneuploidy in several cancer types. Net overexpression of this signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

60
1,050
3
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,047 publications
(1,149 citation statements)
references
References 26 publications
60
1,050
3
6
Order By: Relevance
“…UW473 cells were relatively more sensitive to CDDP, MTX, and TMZ treatments and more resistant to DX than UW402 cell line. Although it has been largely described that CIN confers intrinsic multidrug resistance in tumors (Sheltzer and Amon 2011;Lee et al 2011) and consequently poorer prognosis in cancer patients (Carter et al 2006), in our study, UW473 showed a greater CIN phenotype and it was more chemosensitivity than UW402, which could confirm the hypothesis that excessive genomic instability may surpass a threshold compatible with cell viability (Cahill et al 1999). This concept has been recently corroborated in the clinical context through studies reporting a paradoxical relationship between CIN and survival outcome in cancer, being that tumors exhibiting extreme CIN displayed improved prognosis relative to tumors with intermediate levels of CIN Roylance et al 2011;McGranahan et al 2012;Lee and Swanton 2012).…”
Section: Discussionsupporting
confidence: 77%
“…UW473 cells were relatively more sensitive to CDDP, MTX, and TMZ treatments and more resistant to DX than UW402 cell line. Although it has been largely described that CIN confers intrinsic multidrug resistance in tumors (Sheltzer and Amon 2011;Lee et al 2011) and consequently poorer prognosis in cancer patients (Carter et al 2006), in our study, UW473 showed a greater CIN phenotype and it was more chemosensitivity than UW402, which could confirm the hypothesis that excessive genomic instability may surpass a threshold compatible with cell viability (Cahill et al 1999). This concept has been recently corroborated in the clinical context through studies reporting a paradoxical relationship between CIN and survival outcome in cancer, being that tumors exhibiting extreme CIN displayed improved prognosis relative to tumors with intermediate levels of CIN Roylance et al 2011;McGranahan et al 2012;Lee and Swanton 2012).…”
Section: Discussionsupporting
confidence: 77%
“…33,34 Notably, the amplifications of loci containing MDM2 and CDK4 did not significantly correlate with the chromosome instability index, suggesting that these changes might not be randomly secondary to global chromosomal instability. Together with its frequent occurrence, this finding indicated critical roles for MDM2 and CDK4 amplification in the tumorigenesis of a subset of adenosarcomas.…”
Section: Discussionmentioning
confidence: 94%
“…[2] Furthermore, aneuploidy is associated with poor patient survival. [80][81][82][83][84][85][86][87][88][89] The karyotypes observed in cancer are not random, as different cancer types display specific karyotypes. [36,72,90] While certain forms of aneuploidy can be beneficial to tumor growth, the relationship between cancer and CIN remains paradoxical.…”
Section: Cin Can Have Highly Differential Effects On Cellsmentioning
confidence: 99%